Internalization of Character Education in the Theatrical Work Segara Tanpa Tepi: A Study of Implementation in the Performing Arts - I Gusti Made Darma Putra (Universitas Pendidikan Ganesha, 2025)
The development of the times and shifts in social values have led to a weakening of the internalization of character values in people's lives, especially among the younger generation. Based on this, the purpose of this study is to analyze the values of character education contained in the theatrical work Segara Tanpa Tepi. The approach used is a descriptive, qualitative method with an ethnographic approach. The subject of the study is the theatrical work [Segara Tanpa Tepi] as a medium for expressing Hindu character education values. Participants involved in this study were artists and spiritual figures. The selection of participants used a purposive sampling technique. The methods used for data collection included in-depth interviews, participant observation, and documentary studies. The research instruments were interview sheets, observation sheets, and documentation studies. The research data were analyzed using qualitative descriptive methods, following the steps of data reduction, data presentation, and conclusion. The results of the study on understanding Segara Tanpa Tepi, a religious concept that encompasses basic human abilities, are accompanied by contextual views on Dharma Luas, Nyelisik Sangkan Paran, and Margi Uter. In addition, a finding that in packaging his wayang performance, the puppeteer is truly influenced by his fundamental ability factors, namely thinking (idep), speaking (sabda), and acting (bayu). It is concluded that the theatrical work Segara Tanpa Tepi serves as a medium for internalizing character education values rooted in the teachings of Tri Premana and local Balinese Hindu wisdom. Through aesthetic and spiritual experiences, this theater successfully conveys profound moral, religious, and social messages to the community. The implication of this research is that traditional performing arts can be used as an object of study to understand and convey character values, especially in the context of character education that is rooted in local culture and religious values.